2015
DOI: 10.4103/0971-5916.155577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis A virus strains in a tertiary care health set up in north western India

Abstract: Background & objectives:Hepatitis A virus usually causes acute viral hepatitis (AVH) in the paediatric age group with a recent shift in age distribution and disease manifestations like acute liver failure (ALF). This has been attributed to mutations in 5’non-translated region (5’NTR) which affects the viral multiplication. The present study was aimed to carry out the molecular detection and phylogenetic analysis of hepatitis A virus strains circulating in north western India.Methods:Serum samples from in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…On analyzing genetic diversity by 5’UTR region sequencing, 98-100 per cent nucleotide identity was observed in our samples taking wild type HAV GBM/WT RNA (X75215) as control. Our results were in concordance with various other studies reported from India which showed approximately 98-99.9 per cent nucleotide identity 11 31 . However, base substitution was observed in seven samples between nucleotides 500 and 700 of the 5’UTR region.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On analyzing genetic diversity by 5’UTR region sequencing, 98-100 per cent nucleotide identity was observed in our samples taking wild type HAV GBM/WT RNA (X75215) as control. Our results were in concordance with various other studies reported from India which showed approximately 98-99.9 per cent nucleotide identity 11 31 . However, base substitution was observed in seven samples between nucleotides 500 and 700 of the 5’UTR region.…”
Section: Discussionsupporting
confidence: 93%
“…2 ). All the samples showed similarity with other Indian samples from Chandigarh (JX481901-JX481910; JX390729-JX390733) 11 , Shimla (FJ227129-FJ227134) 3 , Kottayam (DQ004690-DQ004693) 2 and samples from Norway (AJ299464) 12 and Japan (AB279734) 13 .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The molecular study of HAV strains is important as it provides data on the molecular epidemiology of this infection and is a useful tool for outbreak investigation . Data on the genetic diversity of simian HAV are limited.…”
Section: Introductionmentioning
confidence: 99%
“…10 The molecular study of HAV strains is important as it provides data on the molecular epidemiology of this infection and is a useful tool for outbreak investigation. 28,29 Data on the genetic diversity of simian HAV are limited. Thus, such studies in captive monkeys can give insights into the diversity of simian strains and can help with investigations into possible sources of HAV infection in primate centers.…”
mentioning
confidence: 99%